LSPR and SAXS studies of starch stabilized Ag-Cu alloy nanoparticles - Singh M.; Sinha I.; Singh A.K.; Mandal R.K. (My University, 2025)
We report the aqueous phase chemical reduction synthesis of starch stabilized Ag-Cu alloy nanoparticles. Changing the proportions of Ag and Cu precursor salts leads to different levels of solid solubility. The variations in the localized surface plasmon resonance (LSPR) absorbance of sols are analyzed from the perspective of nanoparticles composition and their structural features. Small angle X-ray scattering (SAXS) analysis of the Ag-Cu nanoparticles sols shows the formation of mass fractal aggregate nanostructures in all cases. © 2011 Elsevier B.V.